Isolation and Identification of Carbonoclastic Fungi Causing Damage to Prehistoric Paintings in the Maros-Pangkep Karst Area - Khotimah, Nur Husnul; Haedar, Nur; Abdullah, As'adi; Gani, Fuad; Heriadi (International Journal of Applied Biology, 2024)
The carbonoclastic fungi known as a fungi that can produce calcium carbonate crystals (CaCO3) through the urease enzyme produced to hydrolysis of urea contained in the substrate or growth medium. The presence of carbonoclastic fungi is frequently observed in the karst areas cave wall painting, which are a type of ancient artifact. The destruction to the ancient cave artwork is brought on by the fungus. The purpose of this study was to obtain and determine the types of carbonoclastic fungi that cause damage to cave wall paintings in the Maros-Pangkep karst area. Isolation and selection of carbonoclastic fungi were carried out using Christensen Urea Agar medium. The CaCO3 precipitate potential test was carried out by calculating the mass CaCO3 precipitates formed and analysis of ammonia levels and cell biomass produced during the growth period. Fungi identification was performed using the 18S rRNA gene molecular markers. Twenty four fungi isolates obtained from swab samples in Parewe and Bulu Sipong caves, 7 positive isolated belonged to carbonoclastic fungi. The results of CaCO3 precipitates, namely isolate Ps3 producing precipitates of 80,30 mg with ammonia content value of 701,7064 ppm and cell biomass of 333,80 mg. The identification results showed that Ps3 isolate belongs to Aspergillus sp. strain BW1.